2015
DOI: 10.1038/srep18011
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage development requires the function of Estrogen-related receptor alpha that directly regulates sox9 expression in zebrafish

Abstract: Estrogen-related receptor alpha (ESRRa) regulates a number of cellular processes including development of bone and muscles. However, direct evidence regarding its involvement in cartilage development remains elusive. In this report, we establish an in vivo role of Esrra in cartilage development during embryogenesis in zebrafish. Gene expression analysis indicates that esrra is expressed in developing pharyngeal arches where genes necessary for cartilage development are also expressed. Loss of function analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
(34 reference statements)
1
19
0
Order By: Relevance
“…Given that Slc25a17 acts as a potential peroxisomal transporter of essential cofactors such as CoA, FAD, and NAD + , we reasoned that Slc25a17 might play a crucial role in peroxisome number and function. We found that the number of peroxisomes had not changed by slc25a17 knockdown, as similar levels of the peroxisome‐targeted RFP signals between control and MO slc25a17 ‐injected Tg ( ef1α:RFP‐SKL ) transgenic embryos were detected (Figure c; Kim et al, ). To examine peroxisome‐dependent functions involved in the oxidation of very long‐chain fatty acids and the synthesis of ether phospholipids (also known as plasmalogens), we analyzed the expression of genes involved in fatty acid oxidation or plasmalogen synthesis.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Given that Slc25a17 acts as a potential peroxisomal transporter of essential cofactors such as CoA, FAD, and NAD + , we reasoned that Slc25a17 might play a crucial role in peroxisome number and function. We found that the number of peroxisomes had not changed by slc25a17 knockdown, as similar levels of the peroxisome‐targeted RFP signals between control and MO slc25a17 ‐injected Tg ( ef1α:RFP‐SKL ) transgenic embryos were detected (Figure c; Kim et al, ). To examine peroxisome‐dependent functions involved in the oxidation of very long‐chain fatty acids and the synthesis of ether phospholipids (also known as plasmalogens), we analyzed the expression of genes involved in fatty acid oxidation or plasmalogen synthesis.…”
Section: Resultssupporting
confidence: 54%
“…Control, and slc25a17 or slc25a17l knockdown embryos were collected at various developmental stages, fixed in 4% paraformaldehyde, and processed for in situ hybridization or immunostaining as previously described (Kim et al, ). For immunostaining, antibodies to detect acetylated tubulin (antiacetyl tubulin, 1:500, Sigma‐Aldrich), peroxisomal PMP70 (anti‐PMP70, 1:500, Abcam, Cambridge, United Kingdom), and secondary Alexa Fluor‐conjugated antimouse antibodies (1:400, Invitrogen) or antirabbit (1:400, Invitrogen) antibodies were used.…”
Section: Methodsmentioning
confidence: 99%
“…All experiments were approved by the Gwangju Institute of Science and Technology Animal Care and Use Committee. Experimental OA was induced in 10-week-old male mice by DMM surgery, or by IA injection (once weekly for 3 weeks) of adenovirus (1 × 10 9 plaque-forming units [PFUs] in a total volume of 10 μl) expressing ERRγ (Ad- Esrrg ), ERRα (Ad- Esrra ), ZIP8 (Ad- Slc39a8 ), or HIF-2α (Ad- Epas1 ) 10 13 , 29 . Where indicated, male mice of various ages (8, 12, 16, and 20 weeks old) were used for experimental OA studies.…”
Section: Methodsmentioning
confidence: 99%
“…The roles of ERRs in cartilage biology are beginning to be investigated, with most studies focusing on the functions of ERRα 26 . For instance, studies have shown that ERRα activates the Sox9 promoter in a rat chondrogenic cell line 27 and rat mandibular condylar chondrocytes 28 , and is required for cartilage development in zebra fish 29 . In contrast, cartilage-specific ERRγ transgenic (Tg) mice exhibit chondrodysplasia, in which repressed chondrocyte proliferation decreases the proliferative zone of the growth plate and reduces bone length 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish has two homologues of sox9, sox9a and sox9b. Both Sox9a and Sox9b play roles on neural, cardiac, and cartilage development Zebrafish [60][61][62][63][64] . Network analysis showed that many of these dysregulated transcription factors interact with each other, which suggests that the ethanol-induced developmental defects were the combined and perhaps synergistic effects of multiple regulators and that manipulation of one gene would not lead to complete rescue of ethanol-induced defects.…”
Section: Discussionmentioning
confidence: 99%